Teachers’ knowledge: Teachers’ perceptions and their sources of knowledge in vocabulary instruction - Bekele Daba Shube; Alemu Hailu Hanshu (English Language Teaching Educational Journal, 2022)
The study investigated EFL teachers’ perceptions and their sources of knowledge in vocabulary instruction at the secondary school level in Addis Ababa, Ethiopia. To fulfill this purpose, an explanatory research design and mixed data analysis methods were employed. The study involved thirty-six English teachers from three representative secondary schools. Data was collected from the participant teachers through a questionnaire and a semi-structured interview. The findings show that participants in the study generally have positive perceptions about vocabulary teaching and learning. According to the participants’ perspectives, vocabulary is central to language and it is important to language learners in their language learning. This thought was affirmed by participants in both quantitative and qualitative aspects of the study. The finding also revealed teachers’ sources of knowledge in vocabulary instruction. These knowledge sources include teachers’ teaching experience, their disciplinary background, apprenticeship of observation, and others. The discussion of these findings suggests implications for practices and recommendations for future research to improve vocabulary instruction in secondary schools.